(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This study presents the new elements introduced by the new Insolvency Act as regards the description of insolvency. The Act draws a clear distinction between the civil and criminal consequences of a bankruptcy declaration. In the new law the description is circumscribed to non-culpable bankruptcy and culpable bankruptcy.